Surface Functionalization of Poly(lactic acid) via Deposition of Hydroxyapatite Monolayers for Biomedical Applications - Dopierała, Katarzyna (Langmuir : the ACS journal of surfaces and colloids, 2023)
The surface modification of poly(lactic acid) (PLA) using hydroxyapatite (HAP) particles via Langmuir-Blodgett (LB) and Langmuir-Schaefer (LS) approaches has been reported. The HAP monolayer was characterized at the air/water interface and deposited on three-dimensional (3D) printed poly(lactic acid). The deposition of HAP particles using the LS approach led to a larger surface coverage in comparison to the LB method, which produces a less uniform coating because of the aggregation of the particles. After the transfer of HAP on the PLA surface, the wettability values remained within the desired range. The presence of HAP on the surface of the polymer altered the topography and roughness in the nanoscale, as evidenced by the atomic force microscopy (AFM) images. This effect can be beneficial for the osteointegration of polymeric implants at an early stage, as well as for the reduction of the adherence of the microbial biofilm. Overall, the results suggest that the LS technique could be a promising approach for surface modification of PLA by hydroxyapatite with respective advantages in the biomedical field